Berat Non Karkas Burung Puyuh Jantan Fase Grower Finisher Yang Di Beri Ransum Limbah Tauge Fermentasi - Victor Lenda Landu Praing; I Dewa Nyoman Sudita; I. G. A. Seri Rejeki (GEMA AGRO, 2022)
Sprouts waste is a potential source of poultry feed and its availability is quite a lot in the market. The purpose of this study was to determine the effect of giving fermented bean sprouts flour in the ration of 5 weeks old male quail on the weight of non-carcass grower-finisher phase, and to determine the fermentation level of bean sprouts flour waste in the ration affecting the non-carcass weight of quail. The study was conducted using a completely randomized design (CRD) with 4 treatments and 4 replications. Each replication consisted of 3 male quail, so the number of male quails used was 48. The treatments applied in this study were as follows rations without fermented bean sprouts flour as a control and rations containing fermented bean sprouts waste flour 5%, 10%, and 15%. The parameters observed were blood weight, reed, legs, head, and neck. The data obtained were analyzed for variance. From the results of the study that the provision of fermented bean sprouts waste flour in the commercial ration of male quail in the grower-finisher phase showed insignificant differences (P> 0.05) on blood, reeds, legs, head, and neck, except for intestinal weight. real (P <0.05) at the 15% level. From this research, it can be concluded that giving tougeh waste flour has no effect on the non-carcass grower-finisher phase